Insatiable appetite : the United States and the ecological degradation of the tropical world - Tucker, Richard P., 1938- (University of California Press, 2000)
This text presents a history of the transformation of the tropics in modern times, pointing ultimately to the declining biodiversity that has resulted from the domestication of widely varied natural systems.